A new species of Blaesodactylus (Squamata: Gekkonidae) from Tsingy limestone outcrops in Namoroka National Park, north-western Madagascar - Ineich, Ivan; Glaw, Frank; Vences, Miguel (Zootaxa, 2016)
We describe a new gekkonid lizard of the genus Blaesodactylus from Tsingy limestone of a deciduous dry forest of Namoroka National Park, north-western Madagascar. Blaesodactylus victori sp. nov., the sixth recognized species of this genus, is distinguished from all other congeners by its large size and a combination of regular small gular granules, spotted venter, lack of dorsal tubercles, enlarged supranasal scales separated ventrally by a much smaller scale in contact with the rostral, and black naris. The new arboreal species is also characterized by its dark dorso-ventral stripes on the head separating infralabial and most supralabial plates and in life by a typical white spotted pattern on a washed grey to dark grey vermiculated dorsum. Molecular phylogenetic data place the species into a clade with B. boivini and B. microtuberculatus, as sister to a subclade containing these two species. The new species shares some morphological characters states with its African sister genus Homopholis, suggesting that its morphology might be rather plesiomorphic. We also identify several previously overlooked morphological traits characterizing the entire B. boivini clade, possibly also being plesiomorphic. Due to its extremely limited presumed extent of occurrence and continuing decline of its habitat we propose an IUCN Red List status of "Critically Endangered" for the new species.